Construction of a simulation model of the system "striker-tool-processed medium" - Slidenko, Viktor; Slidenko, Oleksandr; Zamaraeva, Oksana; Novykov, Anton; Tkachenko, Vladyslav (Eastern-European Journal of Enterprise Technologies, 2025)
This study investigates the process of impulse interaction between the elements of an impact device and the processed medium (PM). The task addressed is to combine simulation and mathematical modeling of the process. A simulation model of the striker has been constructed using the Ansys programming system. The basic elements of the striker were built in a geometric shape close to cylindrical; a PM simulator was developed in the Design Modeler module. The degrees of freedom of the elements, their physical properties and external factors were adopted in accordance with the structural scheme and operating modes of the striker. Adequacy of the simulation model was assessed by comparison with discrete and discrete-continuous models. The finite difference method was used to solve the system of differential equations under given initial and boundary conditions. The comparison was carried out by the parameters of impact interaction: co-impact time, vibrations of the contact and impact ends of the tool. Strikers and tools of different sizes with flat contact ends were considered. The impact time was determined by the difference in speeds and displacements of the contact ends of the striker and the tool; it is 0.1–0.5 ms. In this case, the striker speed varied in the range of 3–20 m/s. High-frequency oscillations of the tool ends amounted to 3000–6000 Hz and were determined by the dimensions of the striker and the tool. The discrepancy of the parameters relative to the Ansys system did not exceed 10%. The simulation model has made it possible to evaluate the energy transformation in the “striker-tool-processed medium” system. The coefficient of energy transfer to PM from the tool is 0.55–0.65; from the striker to the tool – 0.75–0.8. The results lay the foundation for applying the simulation model to conduct numerical experiments involving elements of a striking device of complex geometric shape. The simulation model and discrete-continuous models could be used to select rational parameters when designing striking devices